2011
DOI: 10.3390/md9020278
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in Marine Animals

Abstract: Marine animals contain various carotenoids that show structural diversity. These marine animals accumulate carotenoids from foods such as algae and other animals and modify them through metabolic reactions. Many of the carotenoids present in marine animals are metabolites of β-carotene, fucoxanthin, peridinin, diatoxanthin, alloxanthin, and astaxanthin, etc. Carotenoids found in these animals provide the food chain as well as metabolic pathways. In the present review, I will describe marine animal carotenoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
271
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(276 citation statements)
references
References 53 publications
(89 reference statements)
3
271
1
1
Order By: Relevance
“…It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 chemical structure) is a common pigment found in algae, fish, and birds. 1,2) Asx has been reported to be more effective than a representative carotenoid, β-carotene, for prevention of singlet oxygen, as well as lipid peroxidation in biological membranes. [3][4][5][6][7] The direct radical scavenging capability of Asx has been confirmed using the synthetic radical 1,1-diphenyl-2-picrylhydrazyl.…”
mentioning
confidence: 99%
“…As in other red marine fish 7,8 , we found astaxanthin to be a major component 84.3 of total carotenoids, the sum of diester, monoester, and free forms along with yellow xanthophylls such as tunaxanthin 7.3 . Adonirubin 3.7 sum of ester and free forms was also present.…”
Section: Resultsmentioning
confidence: 84%